Effect of Cash Turnover, Receivable Turnover, Inventory Turnover and Growth Opportunity on Profitability - Abd. Rauf Wajo (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2021)
The purpose of this study is to analyze cash flow, accounts receivable turnover, inventory turnover, and growth opportunity for the profitability of manufacturing companies listed on the Indonesia Stock Exchange. This research was conducted at manufacturing companies listed on the Indonesia Stock Exchange. This study's population were manufacturing companies listed on the Indonesia Stock Exchange in 2013-2016, totaling 137 companies. The number of samples used in this study was 16 companies using the purposive sampling method. The data was collected using the documentation method. The type of data used is quantitative, while the data source used is secondary data. This study indicates that cash turnover has a positive and significant effect on profitability, accounts receivable turnover has a positive and significant impact on profitability, has a positive and significant impact on profitability, and growth opportunity has a positive and insignificant effect on profitability.